2014
DOI: 10.4238/2014.july.24.21
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of molecular biomarkers in esophageal carcinoma in different nationalities patients in Xinjiang

Abstract: ABSTRACT. This study aimed to explore some useful biomarkers to focus on the diagnosis and therapy response judgment in esophageal squamous cell carcinoma in Xinjiang. We used enzyme-linked immunosorbent method and immunohistochemistry to detect the expression of VEGF, EGFR, ES, HER-2, and NF-κBp in the serum and tissue with esophageal squamous cell carcinoma, and to analyze the relationship between biomarkers and clinical pathology and curative effects. Our findings were as follows: 1. The serum levels of VEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Previous studies have reported EGFR overexpression in 27-55% of esophageal and GEJ adenocarcinomas (24)(25)(26)(27). Wang et al demonstrated EGFR overexpression in 32% of patients and was correlated with higher tumor stage, lymph node metastasis, but failed to show correlation with shorter disease-free (DFS) or OS, which is in accordance with the results of our study (28).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have reported EGFR overexpression in 27-55% of esophageal and GEJ adenocarcinomas (24)(25)(26)(27). Wang et al demonstrated EGFR overexpression in 32% of patients and was correlated with higher tumor stage, lymph node metastasis, but failed to show correlation with shorter disease-free (DFS) or OS, which is in accordance with the results of our study (28).…”
Section: Discussionsupporting
confidence: 83%
“…In our study of previously untreated tumors, we noted a relatively high expression of EGFR receptor (73%). Previous studies have reported EGFR overexpression in 27-55% of esophageal and GEJ adenocarcinomas (24)(25)(26)(27). Wang et al demonstrated EGFR overexpression in 32% of patients and was correlated with higher tumor stage, lymph node metastasis, but failed to show correlation with shorter disease-free (DFS) or OS, which is in accordance with the results of our study (28).…”
Section: Discussionsupporting
confidence: 92%
“…For domain 2 (“Study Attrition”), 73 original studies showed a low risk of bias because of the high follow-up rate for study participants. Seven original studies had moderate bias in domain 2 due to missing data on participants that were lost to follow-up [ 19 25 ]. There was a high risk of bias in domain 2 in 2 studies because of high loss to follow-up rates (50 and 23%) [ 11 , 26 ].…”
Section: Resultsmentioning
confidence: 99%